2003
DOI: 10.1111/j.1365-2249.2004.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies recognizing citrullinated rat filaggrin in an ELISA using citrullinated and non-citrullinated recombinant proteins as antigens are highly diagnostic for rheumatoid arthritis

Abstract: SUMMARYThe objective of the study was to determine the diagnostic value for rheumatoid arthritis (RA) of antifilaggrin autoantibodies (autoAb) recognizing citrullinated recombinant rat filaggrin (ACRF) in community cases of very early arthritis. To evaluate the diagnostic value of ACRF, were studied sera from patients with different classified rheumatic diseases and healthy subjects (group 1, n = 422) and 314 community cases of very early arthritis (group 2) that were classified as RA ( n = 176), non-RA ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 28 publications
4
44
1
Order By: Relevance
“…The objective is to develop methods with sensitivity and specifi city for earlier RA diagnosis, more reliable activity markers, and prognostic indicators. Some of the autoantibodies used in RA investigation are as follows: mutated citrullinated vimentin antibodies (anti-MCV); [49][50][51] antikeratin antibodies (AKA); anti-perinuclear factor (APF); 52 antifi laggrin autoantibodies; 53 anti-human citrullinated fi brinogen antibodies (ACF); 54 anti-heterogeneous nuclear ribonucleoprotein A2 autoantibody (anti-RA33); 52 anti-interleukin 1 antibody (anti-IL1); 55 anti-alpha-enolase antibody; 56 and anti-advanced glycation end-products antibody. 57 These antibodies have, in general, good specifi city, but sensitivity lower than that of anti-CCP for diagnosing RA.…”
Section: Other Antibodiesmentioning
confidence: 99%
“…The objective is to develop methods with sensitivity and specifi city for earlier RA diagnosis, more reliable activity markers, and prognostic indicators. Some of the autoantibodies used in RA investigation are as follows: mutated citrullinated vimentin antibodies (anti-MCV); [49][50][51] antikeratin antibodies (AKA); anti-perinuclear factor (APF); 52 antifi laggrin autoantibodies; 53 anti-human citrullinated fi brinogen antibodies (ACF); 54 anti-heterogeneous nuclear ribonucleoprotein A2 autoantibody (anti-RA33); 52 anti-interleukin 1 antibody (anti-IL1); 55 anti-alpha-enolase antibody; 56 and anti-advanced glycation end-products antibody. 57 These antibodies have, in general, good specifi city, but sensitivity lower than that of anti-CCP for diagnosing RA.…”
Section: Other Antibodiesmentioning
confidence: 99%
“…However, only 25% of the anti-CCP-negative patients developed RA, compared with 93% of those who were anti-CCP positive at the beginning of the study (odds ratio [OR] 38). A study by Vittecoq et al obtained similar results (37). Those investigators found that in 314 patients with early arthritis, 90% of those who were anti-CCP positive developed RA 1 year later.…”
Section: Rheumatoid Factors (Rfs) and Anti-cyclic Citrullinated Peptimentioning
confidence: 60%
“…However, 2 of these 3 RA serum samples also had reactivity to the citrullinated peptide by microarray, ELISA and nanotube testing. Antibodies to non-citrullinated filaggrin sequences have recently been reported in the occasional RA patient (Vittecoq et al, 2004).…”
Section: Performance Of the Nanotube Assay Compared To Elisa And Micrmentioning
confidence: 98%